2012
DOI: 10.1088/1748-0221/7/11/p11019
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical studies on the effect of SF6in a glass RPC

Abstract: The India based Neutrino Observatory (INO) collaboration is planning to build a 50 kton magnetized iron calorimeter (ICAL) detector to study neutrino oscillations and measure their associated parameters. ICAL will use 28,800 glass Resistive Plate Chambers (RPCs) of 2 m ×2 m size to be operated in the avalanche mode, as its active detector elements. As a part of detector R & D to develop the RPCs, we studied the effect of Sulfur hexaflouride (SF 6 ) when it is added in small amount to the gas composition used f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…The current depends on the applied voltage and shows a threshold behaviour. Figure 2 represents an equivalent electric circuit for an RPC, suitable for our purposes [8].…”
Section: Results and Discussion 31 V-i Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The current depends on the applied voltage and shows a threshold behaviour. Figure 2 represents an equivalent electric circuit for an RPC, suitable for our purposes [8].…”
Section: Results and Discussion 31 V-i Characteristicsmentioning
confidence: 99%
“…An increased number of low energy particles will be blocked when thicker glass electrode is used. This could be the reason for getting Voltage (kV) 8 8. comparatively lower noise rate for RPCs with thicker electrodes. Moreover, small signals inside the gap would induce signals under threshold on read-out electrodes when the electrode thickness is higher, due to the same reason outlined for the efficiency.…”
Section: Noise Rate Of the Stripmentioning
confidence: 99%
“…Thus the mean of the charge distribution decreases with an increase in the SF 6 concentration as shown in the figure 4a. This behaviour is due to the capture of the electrons in the gas gap by SF 6 because of its high electron affinity (1.05 ± 0.10 eV) [7,8]. This reduces the multiplication of electrons in the gas gap.…”
Section: Charge Distributionmentioning
confidence: 99%
“…Many attempts have been made to simulate and understand the working principle of avalanche and streamer modes of RPC. Most of them are based on either Monte Carlo methods [9][10][11][12][13] or hydrodynamics [14][15][16]. A review of different simulation methods can be found in this reference [17].…”
Section: Introductionmentioning
confidence: 99%